Geography in Britain after World War II Nature, Climate, and the Etchings of Time - Martin, Max; Damodaran, Vinita; D'Souza, Rohan (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
XXI, 231 p. 38 illus., 25 illus. in color.